2021
DOI: 10.1002/ecs2.3348
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the invaluable: park visitors' perceived importance and willingness to pay for urban park trees in Pakistan

Abstract: In complex urban systems, urban parks are rare hot spots of nature, responsible for delivering a range of ecosystem services. Trees are critically important components of urban parks that provide many benefits, and, at the same time, face challenges such as lack of funds, mismanagement, climate change, pests, and diseases. There is a growing need to increase the urban tree cover to sustain urban ecosystems. Successful policymaking requires engagement with all stakeholders, especially park users. An understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 68 publications
1
5
1
1
Order By: Relevance
“…Concerning the first part (A) of our research, we found that the most important demand is the production of oxygen. This result ties in well with previous studies wherein the climate and oxygen-related ES were highly valuated (Gouwakinnou et al 2019 ; Malik et al 2021 ; Martín-López et al 2012 ). The Czech students in environmental fields of study showed greater demand for regulation services than other groups, but interestingly, Chinese students did not have a significantly higher demand for FES in comparison with other groups.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the first part (A) of our research, we found that the most important demand is the production of oxygen. This result ties in well with previous studies wherein the climate and oxygen-related ES were highly valuated (Gouwakinnou et al 2019 ; Malik et al 2021 ; Martín-López et al 2012 ). The Czech students in environmental fields of study showed greater demand for regulation services than other groups, but interestingly, Chinese students did not have a significantly higher demand for FES in comparison with other groups.…”
Section: Discussionsupporting
confidence: 92%
“…Higher education levels positively influence tree growing and retention of TOF Positive Generally positive trend (Arabomen et al, 2021;Blanco et al, 2020;Chameno, 2020;Etshekape et al, 2018;Fernandes et al, 2018;Graça et al, 2018;Hanisah et al, 2012;Jones et al, 2013;Kendal et al, 2012;Lockwood & Berland, 2019;Suchocka et al, (Danquah et al, 2023;Hui & Jim, 2022;Lin et al, 2021;Lockwood & Berland, 2019;Malik et al, 2021) High income does not positively influence people's inclination towards planting trees, and does not positively influence the richness and abundance of trees Negative (Arabomen et al, 2020;Cubino & Retana, 2023;Olive et al, 2013) Landholding size…”
Section: Level Of Educationmentioning
confidence: 99%
“…Inconsistent results (Anglaaere et al, 2011;Arabomen et al, 2020;Basu et al, 2022;Bhebhe et al, 2023;Blanco et al, 2020;Chukwumaucheya, 2012;Collins et al, 2019;Deng et al, 2017;Di Cristofaro et al, 2020;Dorresteijn et al, 2017;Drew-Smythe et al, 2023;Fernandes et al, 2018;Gwedla & Shackleton, 2019;Jeong et al, 2023;Kičić et al, 2022;Kloster et al, 2021;Lamichhane & Thapa, 2012;Locke et al, 2015;Malik et al, 2021;Olive et al, 2013;Olivero-Lora et al, 2020;Pati et al, 2022;Rae et al, 2011;Rašković & Decker, 2015;Saldarriaga et al, 2020;Sambou et al, 2017;Smith & Sullivan, 2014;Speak & Salbitano, 2021;Suchocka et al, 2019;Wei et (Basu et al, 2022;Blanco et al, 2020;Collins et al, 2019;Dainese et al, 2017;Kičić et al, 2022;Ng et al, 2015;Saldarriaga et al, 2020;Sebek et al, 2016;Sibelet et al, 2017;Zhang et al, 2020) b. Provisioning value of tre...…”
Section: Positive/ Negativeunclassified
See 2 more Smart Citations